Pengaruh Budaya Sekolah dan Kompetensi Guru terhadap Prestasi Belajar Siswa di MTs Sirojul Athfal Pancoran Mas Kota Depok - Norman, Efrita; Rochmah, Siti (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
A conducive culture and continuosly updated teacher competency development are crucial factors that are closesly observed to assist student in achieving commendable achievement. The purpose of this reseach are, (1) Find out how much influence school culture has on student achievement, (2) Find out how much influence teacher competence has on student learning achievement, (3) Find out how much the combined influence of school culture and teacher competence affects students learning achievement at Sirojul Athfal High school Pancoran Mas Depok City . The population of this reseach consists of 179 individuals, including all 7Th and 8Th grade student, with a quantitative reseach type,and a sample size of 63 was chosen using the random sampling technique, the data collection technique involves using quistionnaries and dokumentation,data analysis employs descriptive analysis,analysis of prerequisite and hypothesis testing . The result of requirment test used include tests for normality, linearity, multicollinearity and hypothesis testing. In this reseach hypothesis analysis employs simple correlation analysis,simple regression multiple correction , coefficient of determination and F-test. The reseach result indicated that (1) There is a possitive and significant influence between school culture on student learning achievement ,with an influence of 16,3% indicated , with an R value of 0,404 and a coefficient of determination (R2) of 0,163. (2) There is a positive and significant influence between teacher competence and student learning achievement of 25,8% indicated with R value of 0,508 and a coefficient of determination of 0,258. (3) There is a possitive and significant competence on student learning achievement of 30,4% indicated with R value of 0,551and a correlation coefficient of determination of 0,304